Altering Work to Rest Ratios Differentially Influences Fatigue Indices During Repeated Sprint Ability Testing. Issue 2 (February 2016) - La Monica, Michael B.; Fukuda, David H.; Beyer, Kyle S.; Hoffman, Mattan W.; Miramonti, Amelia A.; Riffe, Josh J.; Baker, Kayla M.; Fragala, Maren S.; Hoffman, Jay R.; Stout, Jeffrey R.
Abstract : Abstract: La Monica, MB, Fukuda, DH, Beyer, KS, Hoffman, MW, Miramonti, AA, Riffe, JJ, Baker, KM, Fragala, MS, Hoffman, JR, and Stout, JR. Altering work to rest ratios differentially influences fatigue indices during repeated sprint ability testing. J Strength Cond Res 30(2): 400–406, 2016—This study examined the influence of recovery time on fatigue indices, performance (total work [TW], peak power [PP], and mean power [MP]), and oxygen consumption during repeated sprint ability (RSA) on a cycle ergometer. Eight recreationally-trained men performed 3 RSA protocols consisting of 10 × 6 s sprints with 12 s, 18 s, and 24 s rest intervals between each sprint. Fatigue indices were determined as percent decrement (%Dec) and rate of decline using either a log transform method or standard slope approach for TW, PP, and MP during respective RSA protocols. The maximal V[Combining Dot Above]O2 value in response to given sprint intervals and the minimal V[Combining Dot Above]O2 value in response to given rest periods (V[Combining Dot Above]O2 work and V[Combining Dot Above]O2 rest, respectively) were recorded. A repeated measures analysis of variance was used to analyze all variables. Average V[Combining Dot Above]O2 work was not different among rest interval trials. Average V[Combining Dot Above]O2 rest with 12 s rest was greater than 18 s and 24 s (2.16 ± 0.17 L·min −1, 1.91 ± 0.18 L·min −1, 1.72 ± 0.15 L·min −1, respectively), while 18 s was greater than 24 s. Average TW and MP were greater with 24 s rest than 12 s (4, 604.44 ± 915.98 J vs. 4, 305.46 ± 727.17 J, respectively), with no differences between RSA protocols for PP. No differences in %Dec were observed. Both methods of calculating rates of decline per sprint for PP and TW were greater during 12 s than 18 s or 24 s. Since changes were only noted between the 12 s and 24 s protocols, a 6 s differential in rest intervals may not be enough to elicit alterations in TW, PP, MP, or %Dec in RSA performance. Rate of decline may be a more sensitive measure of fatigue than %Dec.